Analisis permintaan kredit pada Bank BPR Tanggo Rajo Kuala Tungkal - Rimawita Rimawita; Siti Hodijah; Candra Mustika (Konsentrasi Pembangunan Regional dan Publik, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2019)
This study aims to: 1) To analyze the development of interest rates on credit, inflation, economic growth, and demand for credit in banks at BPR Tanggo Rajo. and 2) To analyze the effect of the interest rate on credit, inflation, and economic growth on the demand for bank credit in banks at BPR Tanggo Rajo. Based on the simultaneous test results, the variables of credit interest rates, inflation, and economic growth together have a significant effect on credit demand at BPR Tanggo Rajo. Whereas in the partial only variable interest rates and economic growth have a significant and negative effect on credit demand at BPR Tanggo Rajo, while the inflation variable does not have a significant and negative effect on credit demand for BPR Tanggo Rajo. Keywords: Credit demand, Credit interest rates, Inflation, Economic growth